Investigation of tapered optical fiber transmission properties for sensing applications - Musa, Baktiar (2016)
Tapered optical fibers with waist diameters ranging from micrometer to nanometer attract considerable interest due to their unique properties and wide range of applications.One of their interesting applications is in the area of sensing where it utilizes the large evanescent field results from tapering. Despite the extensive works that have been reported on the applications of tapered fiber, information on geometrical manipulation of the taper and its direct effects towards the properties of optical transmission are still very limited. The geometrical manipulation enables us to choose the optimum taper parameters which is vital in enhancing the performance of photonic devices particularly in sensing environmental changes within the surrounding medium. This work investigates the effects of taper parameters such as waist diameter, waist length, transition lengths and taper angle on the transmission properties of tapered fiber.Applications of tapered fibers in refractive index (RI), temperature and strain sensing are also explored. Symmetrical tapers are used in those applications and the effects of taper parameters on the sensitivity are investigated. The study is further extended to cover modified taper structures where asymmetric tapers are tested for RI sensing. Grapheneoxide(GO) were coated on the tapered region using optical deposition method and the effects of its optical deposition time on the ethanol sensitivity are investigated. Tapered fibers were fabricated using a Vytran 3400 optical glass processing workstation which is capable to precisely taper the fiber according to the pre-determined taper parameter values with high reproducibility. The profiles of the taper were studied extensively and their effects on the transmission behaviors were experimentally carried out. The study aims to provide guidelines on taper parameter selection for tapered fiber-based sensing applications. Based from the results obtained, the optimum taper parameters are suggested to be 5 mm each for transition lengths, 10 mm waist length and 10 μm waist diameter. For refractive index sensing, the highest sensitivity of 3912.4 nm/RIU was obtained with the sample having 28.74 mrad taper angle. Smaller waist diameter is also found to increase sensor sensitivity. For example, when the diameter of the 2_10_2 mm taper was reduced from 15 to 5 μm, the sensitivity increased from 1507.2 to 3795.0 nm/RIU. Effects of taper waist length on sensors sensitivity were studied for temperature and strain sensors. Increasing waist length caused temperature sensitivity to drop from 0.0455 (nm/oC) to 0.0141 (nm/oC). While a shorter taper gives more sensitive response to the temperature changes, a longer taper is more preferable in strain measurements. Generally, the sensitivity of RI sensor fabricated from asymmetric taper recorded a lower sensitivity compared to its symmetrical counterpart. Longer optical deposition period results in a more sensitive response to the presence of ethanol. Two-third increment in sensitivity was observed when the taper was optically deposited with GO for 10 minutes.Further increase in sensitivity is observed when the optical deposition period was extended to 20 minutes.